Teacher Leader: A Conceptual Exploration - Aktaş, Yasemin; Cemaloğlu, Necati (Technium Social Sciences Journal, 2026)
Teacher leadership has become an increasingly significant concept in contemporary educational systems. Rising concerns regarding student underachievement and evolving school needs require teachers not only to serve as transmitters of knowledge but also as leaders who guide school development. Since the 1980s, teacher leadership has shifted from administration-oriented responsibilities toward instructional leadership models. Numerous studies have demonstrated that teacher collaboration strengthens school culture, fosters trust, and enhances professional learning. Two major comprehensive reviews in the literature (York-Barr & Duke, 2004; Wenner & Campbell, 2017) indicate that teacher leadership still lacks a unified definition and that stronger theoretical and empirical research is needed. Therefore, it is considered that other factors related to teacher leadership also need to be investigated. The purpose of this study is to conduct a conceptual analysis of teacher leadership. This study was carried out using the document analysis method. In conclusion, the findings emphasize the need for continued research on teacher leadership and highlight the importance of prioritizing teacher leadership to strengthen educational systems in all respects.